The multidimensional role of social entrepreneurship: a case study approach within an international project context - Ferreiro, Maria de Fátima; Sousa, C.; Vale, S.; Sousa, M. (18th European Conference on Innovation and Entrepreneurhip, 2023)
Social entrepreneurship creates social value and has a multidimensional impact (e.g. economic, environmental, cultural). This is related to the complexity and multidimensional approaches to current societal problems such as climatic changes and socioeconomic crises. The paper explores this multidimensionality by presenting three Portuguese case studies of social entrepreneurship operating in diverse domains. The study is based on primary and secondary data on the selected social enterprises. The analysis explores the motivations and constraints in forming a social enterprise and the impact of entrepreneurial activity. There is evidence of multiple roles played by these entrepreneurial agents, and, therefore, their critical role in the response to the problems that current societies face.